Modern african pentecostal discourse: a textual analysis of prayer texts of a Word of Life Church senior pastor - Manyawu, Andrew T. (Institute of Southern African Studies, 2016)
As the rampant forces of global capitalism relentlessly turn the world into a global village where the socio-economically weak are mercilessly marginalised, Southern Africa experiences a return to spiritualism as a strategy to ensure a sense of security and prosperity despite a gloomy material prognosis. Modern African Pentecostalism flourishes in Lesotho thanks to a discourse that seeks to portray the spirit world as real, tangible and controllable by the ‘anointed’ human being. This paper looks at the prayer text of a Word of Life Church Senior Pastor and co-founder from a perspective of Critical Discourse Analysis. The paper finds that her text depends heavily on contextualisation through the use of indexical meanings to “naturalise” Modern African Pentecostal discourse.